2019
DOI: 10.1007/s10802-019-00574-x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Treatment Expectations on Exposure Process and Treatment Outcome in Childhood Anxiety Disorders

Abstract: Objective: This study examined the relationship between caregivers' and youths' treatment expectations and characteristics of exposure tasks (quantity, mastery, compliance) in cognitivebehavioral therapy (CBT) for childhood anxiety. Additionally, compliance with exposure tasks was tested as a mediator of the relationship between treatment expectations and symptom improvement.Method: Data were from youth (N= 279; 7-17 years old) enrolled in the Child/Adolescent Anxiety Multimodal Study (CAMS) and randomized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…A meta-analysis of 50 randomized trials found a significant, positive effect of SSIs on mental health problems, versus control conditions, at post-intervention (g=.32;Schleider & Weisz, 2017)-an effect comparable to that observed for longer-term therapies lasting 16 weeks on average (g = .46; Weisz et al, 2017). SSIs may also improve treatment expectancies, which predict subsequent engagement and response (Swift et al, 2012;Thiruchselvam et al, 2019;Wu et al, 2020). For instance, relative to a placebo control, a 15-minute, online SSI teaching that emotions are malleable strengthened adults' beliefs that therapy could be effective (Schleider & Weisz, 2018).…”
Section: What Are Single-session Interventions and Why Deliver Them? mentioning
confidence: 89%
“…A meta-analysis of 50 randomized trials found a significant, positive effect of SSIs on mental health problems, versus control conditions, at post-intervention (g=.32;Schleider & Weisz, 2017)-an effect comparable to that observed for longer-term therapies lasting 16 weeks on average (g = .46; Weisz et al, 2017). SSIs may also improve treatment expectancies, which predict subsequent engagement and response (Swift et al, 2012;Thiruchselvam et al, 2019;Wu et al, 2020). For instance, relative to a placebo control, a 15-minute, online SSI teaching that emotions are malleable strengthened adults' beliefs that therapy could be effective (Schleider & Weisz, 2018).…”
Section: What Are Single-session Interventions and Why Deliver Them? mentioning
confidence: 89%
“…Youth compliance and mastery of exposure are associated with better CBT response (Peris et al, 2017). In addition, those with more positive expectations about the value of exposure in therapy are more compliant with practice (Wu et al, 2019), underscoring the importance of psychoeducation. Indeed, compliance with exposure practice mediates the link between treatment expectations and anxiety symptom improvement (Wu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, those with more positive expectations about the value of exposure in therapy are more compliant with practice (Wu et al, 2019), underscoring the importance of psychoeducation. Indeed, compliance with exposure practice mediates the link between treatment expectations and anxiety symptom improvement (Wu et al, 2019). Other work has considered the role of therapeutic alliance and patient engagement, finding evidence for reciprocal relationships throughout the course of treatment (McLeod, Southam‐Gerow, & Kendall, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, clients who report more positive attitudes toward the video lesson are hypothesized to report a greater use of coping skills, given that higher treatment expectations have been linked to greater homework compliance and skills use. 20,21 Collectively, these data highlight the utility of COVID-19-specific digital tools in real-world settings, and can inform the development and dissemination of such content within blended care programs.…”
Section: Introductionmentioning
confidence: 85%